Antioxidant's Activity of Avocado (Persea americana Mill.) Seeds Extract Coating by Nanochitosan - Anggraeny, Dyta; Rumengan, Inneke F. M.; Djarkasi, Gregoria S. S.; Suptijah, Pipih (Jurnal Ilmu dan Teknologi Pangan, 2017)
An increasing production of avocado in Indonesia  has resulted in abundant seeds as wastes. Avocado’s seeds contain potential antioxidant compound, such as phenolic compound, which could be exploited for human consumption. Utilization of seeds as functional food could be more efficient by coating with a certain substance. Chitosan is a bio-compatible and non-toxic compound, and could be used as coating agent in the form of nanochitosan. The purpose of this study was to evaluate the content of  phenolic-compound in extract of avocado’s seed with and without coated by nanochitosan. In this study, the extract of avocado’s seed was coated with  Parrot fish scale (Scarus sp) derived nanochitosan, compared with nanochitosan from crab’s shell. Nanochitosan was prepared from chitosan by gelation ionic method. The results show that avocado’s seed extract has 44.89 mg/Kg of phenolic content,  much lower than the content in the extract coated with nanochitosan of fish and crab shell, which were 84.08  and 113,67 mg/Kg, respectively.   Therefore, coating with nanochitosan was proven increasing the phenolic compound in the extract of avocado’s seed.  Keywords: avocado, nanochitosan, phenol